Benchmark of Delayed Equilibrium Model (DEM) and classic two-phase critical flow models against experimental data. (June 2017) - De Lorenzo, M.; Lafon, Ph.; Seynhaeve, J.-M.; Bartosiewicz, Y.
Highlights: Separate benchmark for critical flow models according to the thermodynamic conditions (saturated - subcooled) and the geometrical configurations (long tubes- short nozzles - slits). Benchmark of the critical pressure, unavailable in literature. Validation of the DEM and classic two-phase critical flow models against more than 450 experimental data. Calculation of mean error and standard deviation for critical mass flux predictions and critical pressure evaluations. Abstract: The safety analysis of Pressurized Water Reactors, in the event of LOCA, strongly depends on the ability to evaluate the discharge rate of coolant inventory through the breach. Due to the huge pressure difference between the primary system and the reactor containment, the mass flow rate is choked at the break. Under such conditions, both mechanical and thermal equilibrium between phases are not ensured. A general theory to evaluate the two-phase critical mass flow rate is not yet available. However, some models are capable of providing accurate evaluations of either critical mass flux or critical pressure and such a model is the Delayed Equilibrium Model (DEM), which is examined in this article. Here we show how to integrate the DEM system of equations coupling a standard Runge-Kutta method with the Possible-Impossible Flow algorithm. Hence a simple procedure which does not require sophisticate computational schemes. The main objective of this work is to compare DEM, Homogeneous Equilibrium Model, Moody (1965) and Henry and Fauske (1971) models to experimental data. The four models were tested and the results from experimental data containing a sample range in excess of 450 conditions compared in determining an appropriate benchmark. Each of the chosen models is representative of a particular category of critical flow models. Furthermore, two-phase critical models provide good estimations depending on the configuration or set of conditions. Consequently, the models have been individually tested incorporating long tubes, short tubes and slits. This analysis has been carried out for both critical mass flux and critical pressure evaluations.